Factors Related to Health Literacy among High Risk Diabetes Mellitus Population in Bangkok Community - Khunasa, Jongkonnee; Koshakri, Rukchanok; Krainuwat, Kerada (Journal of The Royal Thai Army Nurses, 2020)
The purpose of this research was to study the correlation among factors such as income, perceived health status, caregiver, social support, access to care, the 3E 2S policy and health literacy among a high-risk diabetes mellitus population in Bangkok. The sample was 230 high-risk diabetes mellitus, people aged 18 - 59 years, both male and female in Bangkok community. The samples were obtained by simple random sampling by using questionnaires, consisting of a demographic questionnaire, perceived health status questionnaire, social support questionnaire and health literacy questionnaire according to ‘3E 2S’ policy in population at high-risk diabetes mellitus. Data were analyzed by using descriptive statistics, Pearson product - moment correlation coefficient and point-biserial correlation coefficients. The results show that the high risk diabetes mellitus population had moderate overall health literacy (56.1%) and the factors related to health literacy among the high risk diabetes mellitus with statistical significance include income, perceived health status, social support, access to care and the 3E 2S policy. It was found that the factor that was not related to health literacy among the high-risk diabetes mellitus population was care giver From the study, proactive service system model should be developed to enhance health literacy by considering income, perceived health status Social support Providing services that are easily accessible And support awareness and access to 3E 2S policy